Narrativas sobre parentalidad y relaciones con pares de gemelas adolescentes - Cruz Neira, Natalia Yineth; Pulido Conde, Erika Fernanda (Universidad Antonio Nariño, 2023)
The current study was conducted from a systemic perspective and adopted a qualitative approach with a narrative design. Its main objective is to explore and describe the stories and narratives about parenting and peer relationships in adolescent twins. To achieve this purpose, two pairs of adolescent twins participated in the study, sharing their perspective regarding their experiences with family and social relationships during adolescence and as twin sisters. The relevance of the aforementioned aspects was clearly demonstrated throughout the interviews conducted in the study.